2015
DOI: 10.3389/fphys.2015.00258
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic responses after resistance exercise in treated hypertensive subjects

Abstract: The aim of this study was to assess and to compare heart rate variability (HRV) after resistance exercise (RE) in treated hypertensive and normotensive subjects. Nine hypertensive men [HT: 58.0 ± 7.7 years, systolic blood pressure (SBP) = 133.6 ± 6.5 mmHg, diastolic blood pressure (DBP) = 87.3 ± 8.1 mmHg; under antihypertensive treatment] and 11 normotensive men (NT: 57.1 ± 6.0 years, SBP = 127 ± 8.5 mmHg, DBP = 82.7 ± 5.5 mmHg) performed a single session of RE (2 sets of 15–20 repetitions, 50% of 1 RM, 120 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
9
0
2
Order By: Relevance
“…The 473 Ser phosphorylation of the PKB (phosphorylated PKB) activates mTOR through the activation of Rheb (the Ras homolog enriched in the brain), which is the upstream factor of mTOR (Fan et al 2004, Kang & Cho 2015, Meena & Kanwar 2015, Sun et al 2016. Moreover, amino acid can be used as a signal molecule to directly act on the mTOR for activation (Hara et al 1998, Kimball & Jefferson 2006, Dukes et al 2015, Trevizani et al 2015. Activated mTOR improves protein synthesis through the direct phosphorylation of the eukaryotic translation initiation factor 4E-binding protein 1 (4EBP1) and ribosome protein S6 kinase 1 (S6K1).…”
Section: Discussionmentioning
confidence: 99%
“…The 473 Ser phosphorylation of the PKB (phosphorylated PKB) activates mTOR through the activation of Rheb (the Ras homolog enriched in the brain), which is the upstream factor of mTOR (Fan et al 2004, Kang & Cho 2015, Meena & Kanwar 2015, Sun et al 2016. Moreover, amino acid can be used as a signal molecule to directly act on the mTOR for activation (Hara et al 1998, Kimball & Jefferson 2006, Dukes et al 2015, Trevizani et al 2015. Activated mTOR improves protein synthesis through the direct phosphorylation of the eukaryotic translation initiation factor 4E-binding protein 1 (4EBP1) and ribosome protein S6 kinase 1 (S6K1).…”
Section: Discussionmentioning
confidence: 99%
“…For frequency domain analysis, the RR interval time series will be detrended (smooth prior), resampled at 4 Hz, and decomposed using the fast Fourier transform algorithm. The components of low (LF, 0.04-0.15 Hz) and high (HF, 0.15-0.4 Hz) frequencies will be calculated as described elsewhere [48].…”
Section: Cardiovascular Autonomic Functionmentioning
confidence: 99%
“…In table 1 are presented post-exercise autonomic responses assessed by different methods. Overall, there were reductions of muscle sympathetic nerve activity after aerobic exercise 10,11,52 , reduction of cardiac autonomic balance 14,53 , and increase of baroreflex sensitivity and heart rate variability 54 . Contrarily, other studies reported increased cardiac and vasomotor sympathetic modulation, decreased parasympathetic modulation and/or attenuation of baroreflex sensitivity 12,13,15,55 however, those studies used resistance exercise 13,15,55 or maximal aerobic exercise 12 .…”
Section: Post-exercise Hypotensionmentioning
confidence: 99%
“…Aprile et al 52 9 patients with stages 2-3 chronic kidney disease (50 ± 8 years) and 12 healthy volunteers (50 ± 5 years) Randomized sessions: (1) exercise (45 min, cycle ergometer, 50% of VO2peak) and (2) rest (seated, 45 min).…”
Section: Responses Hemodynamic Autonomicmentioning
confidence: 99%